2002
DOI: 10.1046/j.1365-2435.2002.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between plant litter decomposition, litter quality, and vegetation responses to herbivores

Abstract: Summary1. There is increasing awareness that similar suites of plant traits may govern foliage palatability and litter decomposability, but whether there is an association between the response of vegetation to herbivory and litter decomposition rates across plant species remains unexplored. 2. We collected 141 samples of litter from 59 understorey and 18 canopy tree species from a total of 28 sites under natural forest throughout New Zealand. We assessed whether variables related to decomposition and quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
255
5
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(286 citation statements)
references
References 30 publications
12
255
5
6
Order By: Relevance
“…They also suggested that there is a group of small-leaved shrubs with stems >3 mm diameter that are resistant to mammalian browsing. This is consistent with the results of this study and those of Wardle et al (2002) who found that small-leaved plants, often with stems >3 mm diameter, did not generally benefit from ungulate exclusion in many New Zealand regions. Most experimental studies have failed to show a benefit from the divaricating form for protection from cold, wind or low humidity (Kelly and Ogle 1990;McGlone and Clarkson 1993;Darrow et al 2001), and so defence from herbivory may be the best explanation for this adaptation.…”
Section: Speciessupporting
confidence: 93%
“…They also suggested that there is a group of small-leaved shrubs with stems >3 mm diameter that are resistant to mammalian browsing. This is consistent with the results of this study and those of Wardle et al (2002) who found that small-leaved plants, often with stems >3 mm diameter, did not generally benefit from ungulate exclusion in many New Zealand regions. Most experimental studies have failed to show a benefit from the divaricating form for protection from cold, wind or low humidity (Kelly and Ogle 1990;McGlone and Clarkson 1993;Darrow et al 2001), and so defence from herbivory may be the best explanation for this adaptation.…”
Section: Speciessupporting
confidence: 93%
“…Currently, few studies address how leaf chemistry influences energy flow to herbivores and decomposers simultaneously. However, several reports suggest that antiherbivore defenses may continue to function against decomposers during decomposition (Grime et al 1996;Wardle et al 2002). Patterns of leaf physiology, chemistry and structural defenses identified across this precipitation gradient suggest that lower food quality and higher allocation to structural defenses in wetter forest may contribute to reduced litter quality.…”
Section: Canopy Leaf Structure and Chemistrymentioning
confidence: 96%
“…Overall, the effects of the organic input derived by phytophagous insects affecting fungal and bacterial gene abundance are poorly understood. However, bacteria are known to arrange a rapid turnover of easily decomposable compounds derived from litter, while fungi dominate a turnover of more complex organic compounds [20,21]. In acidic soils of pine forests, denitrification is expected to be an important driver for N turnover as nitrification rates in these "non-nitrifying" ecosystems are often negligibly low [6,22] and the nitrate reduction potential and nitrogen loss via denitrification are shown to be increased in these soils [23].…”
Section: Introductionmentioning
confidence: 99%